PDZK1 Is a Novel Factor in Breast Cancer That Is Indirectly Regulated by Estrogen through IGF-1R and Promotes Estrogen-Mediated Growth - Hogyoung Kim; Zakaria Y Abd Elmageed; Jihang Ju; Amarjit S Nauru; Asim B Abdel-Mageed; Shibu Varughese; Dennis Paul; Suresh Alahari; Andrew Catling; Jong G Kim; A Hamid Boulares (BMC, 2013)
Abstract Although a relationship between PDZK1 expression and estrogen receptor (ER)-α stimulation has been suggested, the nature of such a connection and the function of PDZK1 in breast cancer remain unknown. Human tissue microarrays (cancer tissue: 262 cores; normal tissue: 87 cores) and breast cancer cell lines were used to conduct the study. We show that PDZK1 protein expression is tightly correlated with human breast malignancy, is negatively correlated with age and had no significant correlation with ER-α expression levels. PDZK1 exhibited an exclusive epithelial expression with mostly cytosolic subcellular localization. Additionally, 17β-estradiol induced PDZK1 expression above its basal level more than 24 h after treatment in MCF-7 cells. PDZK1 expression was indirectly regulated by ER-α stimulation, requiring insulinlike growth factor 1 receptor (IGF-1R) expression and function. The molecular link between PDZK1 and IGF-1R was supported by a significant correlation between protein and mRNA levels (r = 0.591, p < 0.001, and r = 0.537, p < 0.001, respectively) of the two factors in two different cohorts of human breast cancer tissues. Interestingly, PDZK1 knockdown in MCF-7 cells blocked ER-dependent growth and reduced c-Myc expression, whereas ectopic expression of PDZK1 enhanced cell proliferation in the presence or absence of 17β-estradiol potentially through an increase in c-Myc expression, suggesting that PDZK1 has oncogenic activity. PDKZ1 also appeared to interact with the Src/ER-α/epidermal growth factor receptor (EGFR) complex, but not with IGF-1R and enhanced EGFR-stimulated MEK/ERK1/2 signaling. Collectively, our results clarify the relationship between ER-α and PDZK1, propose a direct relationship between PDZK1 and IGF-1R, and identify a novel oncogenic activity for PDZK1 in breast cancer.